Effect of Roux-en-Y Bariatric Bypass Surgery on Subclinical Atherosclerosis and Oxidative Stress Markers in Leukocytes of Obese Patients: A One-Year Follow-Up Study - Zaida Abad-Jiménez; Sandra López-Domènech; Segundo Ángel Gómez-Abril; Dolores Periañez-Gómez; Aranzazu M. de Marañón; Celia Bañuls; Carlos Morillas; Víctor M. Víctor; Milagros Rocha (MDPI AG, 2020)
Little is known about the mechanisms underlying the cardioprotective effect of Roux en-Y gastric bypass (RYGB) surgery. Therefore, the aim of the present study was to investigate whether weight loss associated with RYGB improves the oxidative status of leukocytes and ameliorates subclinical atherosclerotic markers. This is an interventional study of 57 obese subjects who underwent RYGB surgery. We determined biochemical parameters and qualitative analysis of cholesterol, leukocyte and systemic oxidative stress markers -superoxide production, glutathione peroxidase 1 (GPX1), superoxide dismutase (SOD) activity and protein carbonylation-, soluble cellular adhesion molecules -sICAM-1 and sP-selectin-, myeloperoxidase (MPO) and leukocyte-endothelium cell interactions-rolling flux, velocity and adhesion. RYGB induced an improvement in metabolic parameters, including hsCRP and leukocyte count (p < 0.001, for both). This was associated with an amelioration in oxidative stress, since superoxide production and protein carbonylation were reduced (p < 0.05 and p < 0.01, respectively) and antioxidant systems were enhanced (GPX1; p < 0.05 and SOD; p < 0.01). In addition, a significant reduction of the following parameters was observed one year after RYGB: MPO and sICAM (p < 0.05, for both), sPselectin and pattern B of LDL particles (p < 0.001, for both), and rolling flux and adhesion of leukocytes (p < 0.05 and p < 0.01, respectively). Our results suggest that patients undergoing RYGB benefit from an amelioration of the prooxidant status of leukocytes, metabolic outcomes, and subclinical markers of atherosclerosis.